Behavioural Realism and Its Impact on Virtual Reality Social Interactions Involving Self-Disclosure - Alan Fraser; Ross Hollett; Craig Speelman; Shane L. Rogers (Applied Sciences)
This study investigates how the behavioural realism of avatars can enhance virtual reality (VR) social interactions involving self-disclosure. First, we review how factors such as trust, enjoyment, and nonverbal communication could be influenced by motion capture technology by enhancing behavioural realism. We also address a gap in the prior literature by comparing different motion capture systems and how these differences affect perceptions of realism, enjoyment, and eye contact. Specifically, this study compared two types of avatars: an iClone UNREAL avatar with full-body and facial motion capture and a Vive Sync avatar with limited motion capture for self-disclosure. Our participants rated the iClone UNREAL avatar higher for realism, enjoyment, and eye contact duration. However, as shown in our post-experiment survey, some participants reported that they preferred the avatar with less behavioural realism. We conclude that a higher level of behavioural realism achieved through more advanced motion capture can improve the experience of VR social interactions. We also conclude that despite the general advantages of higher motion capture, the simpler avatar was still acceptable and preferred by some participants. This has important implications for improving the accessibility of avatars for different contexts, such as therapy, where simpler avatars may be sufficient.